2016
DOI: 10.1007/s11738-016-2166-y
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin expediently modifies proteome of maize (Zea mays L.) embryo during seed germination

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) has a great potential for plant biostimulation. Its role in plant physiology is intensively explored, and its important function in plant stress defence frequently underlined. Melatonin is particularly effective when applied as an additional factor of seed priming. In the presented research, hydroconditioning was chosen experimentally as optimal for maize (Zea mays L.) seeds. The following seed variants were compared: controlled non-treated, hydroprimed with water and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…It is also worth mentioning that transcriptome analysis of melatonin-treated Arabidopsis (Weeda et al, 2014 ) revealed upregulation of numerous genes implicated in the signaling of senescence-promotion but also stress-induced phytohormones, such as ethylene, abscisic, jasmonic, and salicylic acids (Jibran et al, 2013 ; Khan et al, 2014 ). This also might indicate that MEL provokes a stress response syndrome in plants as suggested by Kołodziejczyk et al ( 2016a , b ), although this issue still requires clarification. Since the breakdown of the damaged Chl and de novo synthesis are a natural processes occurring in plant cells, the next step was to examine if under oxidative stress MEL affects the contents of its precursor-ALA. Biosynthesis of ALA is the first step of Chl biosynthesis, and is therefore supposed to be a crucial control point in the regulation of Chl supply (Figure 2 ; Tanaka and Tanaka, 2006 ).…”
Section: Discussionmentioning
confidence: 85%
“…It is also worth mentioning that transcriptome analysis of melatonin-treated Arabidopsis (Weeda et al, 2014 ) revealed upregulation of numerous genes implicated in the signaling of senescence-promotion but also stress-induced phytohormones, such as ethylene, abscisic, jasmonic, and salicylic acids (Jibran et al, 2013 ; Khan et al, 2014 ). This also might indicate that MEL provokes a stress response syndrome in plants as suggested by Kołodziejczyk et al ( 2016a , b ), although this issue still requires clarification. Since the breakdown of the damaged Chl and de novo synthesis are a natural processes occurring in plant cells, the next step was to examine if under oxidative stress MEL affects the contents of its precursor-ALA. Biosynthesis of ALA is the first step of Chl biosynthesis, and is therefore supposed to be a crucial control point in the regulation of Chl supply (Figure 2 ; Tanaka and Tanaka, 2006 ).…”
Section: Discussionmentioning
confidence: 85%
“…One of the leading theories for the function of melatonin in mitigating diverse stresses, including thermal stress, is that it reduces ROS and free radicals produced in response to these stresses either directly or via upregulation of other related pathways, such as the ascorbate‐glutathione cycle, though many other mechanisms have also been identified such as interaction with phytohormone networks, or modification of protective transcription factors . Melatonin applied to seeds also modifies their proteome when germinated under optimal (prevention) and chilling stress (intervention) conditions . If melatonin is effective in combatting stress in this way, it would need to be present in cells under stress.…”
Section: Discussionmentioning
confidence: 99%
“…There are suggestions that seed conditioning may be a method of improving tolerance through ‘priming memory’ (Savvides et al, 2016). Generally it is provoked by induction of stress reaction syndrome without negative metabolic disorders and injuries, e.g., through epigenetic modifications and/or synthesis of corresponding anti-stress proteins (Kołodziejczyk et al, 2016a,b). …”
Section: Discussionmentioning
confidence: 99%